(untitled) (De Musica, 2024)
In this paper, I analyze how the auditory system works when exposed to different kinds of music components, such as melodies, harmonies, the mere successions of sounds, and the ordinary simultaneities of sounds. I will claim that, while melodies and harmonies are perceivable, the mere successions of sounds and the ordinary simultaneities of sounds are processed at the cognitive level. This conclusion is based on the analysis of how the auditory system employs primitive grouping, schema-based grouping, and cognitive schema-based grouping when ordering the auditory landscape by the identification and categorization of meaningful musical streams.